Comparison of clinical presentation between Chronic Otitis Media Mucosal with Squamous. - Shrestha, B L; Shrestha, I; Amatya, R C (Kathmandu University Medical Journal, 2012)
Background Chronic otitis media is a chronic inflammatory disease of the middle ear cleft which is manifested as deafness and ear discharge. It is a common condition affecting 0.5 – 30% of any community worldwide, and most common in developing countries. The prevalence mainly depends on age, low socio-economic status, overcrowding and limited medical facilities. Objective To compare the clinical presentation between chronic otitis media mucosal with squamous types. Methods A prospective, longitudinal and analytical study performed among 200 patients who have features of chronic otitis media and were attended to in the ear, nose and throat outpatient department of Dhulikhel Hospital - Kathmandu University Hospital, Dhulikhel, Nepal from January 2010 to January 2011. Patients who had already undergone surgery and came back to the hospital, with inadequate information were excluded from the study. Results The results showed that, out of 200 cases, 120 (60%) were chronic otitis media- mucosal and 80 (40%) were chronic otitis media – squamous. Patients < 30 years were affected in both groups. The male to female ratio in chronic otitis media mucosal was 1.14:1, whereas in chronic otitis media squamous, it was 1.96:1. Similarly in etiological factors, oil and water exposure (76%) was the most common cause in chronic otitis media mucosal, whereas in chronic otitis media squamous, oil and water exposure (62.5%) and recurrent upper respiratory tract infection (62.5%) were the most common causes. Of all the clinical features, ear discharge was the leading feature in both chronic otitis media mucosal (98%) and squamous (100%) cases. The complications were mainly seen in the chronic otitis media squamous and the most common complication was mastoid abscess (5%). Conclusions The frequency of chronic otitis media is higher in the younger age group and those lacking in health education. As a result, it is important to disseminate the health education regarding the ear disease which will help in decreasing the frequency of the disease in developing countries like ours. http://dx.doi.org/10.3126/kumj.v8i4.6237 Kathmandu Univ Med J 2010;8(4):387-91